Lathinen, A. (2018). China’s Diplomacy and Economic Activities in Africa. Relations on the Move, Palgrave Macmillan, 107 páginas - Marchetti, Agustina (2019)
Fil: Fil: Marchetti, Agustina. Universidad Nacional de Rosario; Argentina